Pendampingan Pembelajaran pada Masa Pandemi di Madrasah Ibtidaiyah Nurul Huda Desa Taji Sekaran - Khubni Maghfirotun,; Khofifah, (TAAWUN, 2021)
The impact that was given because of the coronavirus pandemic entered to the corners of the village, one of which is Taji Village, Maduran District, Lamongan Regency. The impact is on educational activities, economy, religious activities, social activities, and government. Government policy with the implementation of new normal has been implemented by the community of Taji Village residents, but the activities carried out are considered less or ineffective so as to make the community restless and even desperate. furthermore, the PKM team conducted devotion and mentoring activities that were carried out from July 27 to August 31, 2020 witha focus on devotion in learning assistance in Madrasah Ibtida'iyah Nurul Huda Taji village is a 6th grade student with a total of 6 students. The startegi used in this devotion is 1. It is located in the village where students live. 2. Done by developing a network with the Village Government. 3. Done by developing a network with the Principal. In an effort to continue to carry out learning activities effectively in this new normal, the PKM team conducts direct learning assistance to learners during face-to-face hours and during onlinelearninghours. With this assistance, the obstacles that arise in the learning process at MI NURUL HUDA Taji village when there is a phenomenon of Covid-19 virus attack can be overcome.